Implementasi BUMDes dalam Meningkatkan Pembangunan Desa Studi Kasus BUMDes Hardjo Utomo Desa Sukoharjo Kecamatan Sukoharjo Kabupaten Wonosobo - Anita Anita (Transformasi Hukum, 2022)
The presence of PP No. 11 of 2021 also regulates the strengthening of BUMDes. Things that are regulated are activities and units of BUMDes as legal entities BUMDes can directly run their business (Operating Company) or become the parent for business units with legal entities (Investment Company). Village BUMDes and lastly also discussed about the capital and assets of BUMDes that must be protected. The problem is whether PP 11 of 2021 can be understood and implemented by the Village Government and the BUMDes Management itself. How do we take a closer look at the constraints and their implementation. In this study, the research method used is sociological empirical research that emphasizes the goal of obtaining legal knowledge empirically by conducting field surveys to the object directly. The data obtained will be analyzed qualitatively, namely by discussing and describing the results of research based on applicable laws and regulations, legal facts, provisions, books and scientific papers as references and data obtained to answer existing problems. The results showed that the implementation of BUMDes in Harjo Utomo in Improving Village Development Based on PP No. 11 of 2021 in Sukoharjo Village, Sukoharjo District, Wonosobo Regency. Based on Law No. 6 of 2014 Article 78 paragraph 2 states that village development includes stages: planning stage, implementation stage and supervision stage. The contribution of Hardjo Utomo BUMDes in increasing development for the village government in Sukoharjo Village in this case physical development and human development (community empowerment) actually has its own work program or development program, so this BUMDes is in nature to support the Village budget, the results of the BUMDes enter the APDES from the PEMDES who will deposit it according to the authority of the village. For physical development, such as building a non-physical market then employing people with disabilities and creating new jobs.